Health System Guidance as Nursing Intervention for Ineffective Health Management in Aggregate Adults with Hypertension - Sholikhah, Rahma Mar'atus; Ati, Niken Asih Laras; Kurdi, Fahruddin; Ardhani, Ni Ketut (Jurnal Kesehatan Komunitas Indonesia, 2024)
Introduction: Hypertension is a type of non-communicable disease that can significantly cause morbidity and mortality of sufferers. Adult age is a risk factor that has a great influence on hypertension. Interventions that can be given to the community are Health System Guidance to identify hypertension problems in the community and develop the ability to overcome existing health problems, namely hypertension problems. Objective: To determine the effectiveness of nursing interventions for health system guidance. Method: Descriptive and analytical research design with a sample of 50 productive age who have hypertension in the RW 08 area of Patrang Village and 5 health cadre. This research carried out implementation in the form of primary prevention (health education), secondary prevention (hypertension screening and cadre empowerment) and tertiary prevention (education and demonstration of giving star fruit juice). Data collection used respondent characteristic instruments, hypertension knowledge questionnaire, hypertension diet questionnaire, standart operating procedure for blood pressure measurement, standart operating procedure for making star fruit juice. Data analysis used paired sample t-test, wilcoxon test, and mann whitney test. Results: There was a significant difference between knowledge before health education and after health education (p = 0.000). In cadre empowerment, there was an increase in the percentage of cadre ability and the mean of cadre knowledge. In tertiary prevention, there was a significant difference between blood pressure after giving star fruit juice therapy between the intervention and control groups (p < 0.05). Conclusion: Health system guidance is effective in improving health management of hypertension.